Dynamics and Vibration / An Introduction - Wahab Magd Abdel (John Wiley & Sons, Ltd, 2008)
This book offers lectures and students of Dynamics and Vibration a practical and concise resource specifically for their needs. Preface, Acknowledgements, Dynamics, Kinematics of Particles, Kinematics of Rigid Bodies, Balancing of Machines, Vibration, Free Vibration of Systems with a Single Degree of Freedom, Forced Vibration of Systems with a Single Degree of Freedom, Vibration of Continuous Systems, Finite-Element Method, Appendices, DAMA and Guidelines for Simulations, Properties of Area, Equivalent Stiffness for Combinations of Springs, Summary of Formulas, Index.